Level of Knowledge of Harvest Employees about Oil Palm Harvesting Techniques at PT. Alam Jaya Persada - Sri Ngapiyatun; Sania Mafazatin Nailia; Erna Rositah; Rossy Mirasari; Rusli Anwar; Wartomo; Humairo Aziza; Ahmad Zamroni (Jurnal Loupe, 2025)
The increase in the number of areas of oil palm plantations and technology that continues to develop has an impact on the increasing need for human resources, especially labor. There are several stages of work in oil palm plantations that require special attention, one of which is oil palm harvesting work because this work requires skills other than physical strength. Harvesters are required to be skilled in harvesting and have knowledge of correct harvesting techniques both in terms of harvest quality and quantity because this work is directly related to fresh fruit bunches (FFB). The research aims to determine the characteristics and level of knowledge of harvesters regarding palm oil harvesting techniques. The data used is questionnaire data as primary data. Before being distributed to respondents, the questionnaire was tested for validity, then continued with a reliability test. The data was analyzed using mathematical calculations. Employees at PT. Alam Jaya Persada is male with 100%. The age of 100% harvest employees falls within the productive age group, namely 18-53 years. The majority of education, 69.4%, only received elementary school education. Workers who work between 1 year and more than 5 years amount to 75%.  Employee knowledge of palm oil harvesting techniques is included in the Good category.